An Evaluation of First-Come, First-Served Scheduling in a Geometrically-Constrained Wet Bulk Terminal - Eisen, Heleen E.; Van der Lei, Joachim E.; Zuidema, Joost; Koch, Thomas; Dugundji, Elenna R. (Frontiers in Future Transportation, 2021)
In 2022, a new sea lock at IJmuiden is expected to open, permitting an increase in marine traffic of larger ships from the sea to the port. In the interest of facilitating operations, we evaluate the impact of the current first-come, first-served (FCFS) admittance policy in the context of berth allocation for a wet bulk terminal in the port. Four model types are constructed: optimal FCFS; no FCFS with fixed arrival times; 48-hour arrival time relaxation; and complete arrival time relaxation. Comparison of the model types is done by means of a rolling time window: of each day within the time frame, a schedule was created for the following two weeks, after which the objective value was calculated. When comparing the average of all objective values, it was found that the optimal FCFS model already shows an improvement compared to the historical situation. Between the FCFS and the no FCFS model, there are no considerable differences, because the vessels are constrained to be scheduled on/after their arrival time at the port. When relaxation is allowed, a considerable efficiency gain is possible, especially if larger ships arrive at the port.